Cognitive Function in Girls with ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Neuropsychological performance of 43 girls, aged 6 to 17 years, with ADHD and 36 controls without ADHD was assessed at the Massachusetts General Hospital, Boston.